2022
DOI: 10.1002/jcp.30730
|View full text |Cite
|
Sign up to set email alerts
|

N6‐methyladenosine modification participates in neoplastic immunoregulation and tumorigenesis

Abstract: This review aims to provide insight into the role of N6‐methyladenosine (m6A) modification in neoplastic immunity and subsequent tumorigenesis. m6A modification, which is catalyzed by methyltransferases, demethylases and reader proteins, has emerged as a widespread regulatory mechanism that controls immune‐related gene expression and immune reactions during tumorigenesis. Aberrant m6A modification changes the neoplastic immune response in multiple cancers by regulating immune cell infiltration, tumor‐promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…N6-methyladenosine (m6A) is the most common modification in the mammalian RNA transcriptome and is broadly present in mRNAs and certain noncoding RNAs [ 41 ]. Recent studies have suggested that alterations in m6A modification patterns are deeply involved in tumorigenesis [ 42 ]. Methyltransferase-like 14 ( METTL14 ) is a key RNA methyltransferase involved in m6A modification.…”
Section: Discussionmentioning
confidence: 99%
“…N6-methyladenosine (m6A) is the most common modification in the mammalian RNA transcriptome and is broadly present in mRNAs and certain noncoding RNAs [ 41 ]. Recent studies have suggested that alterations in m6A modification patterns are deeply involved in tumorigenesis [ 42 ]. Methyltransferase-like 14 ( METTL14 ) is a key RNA methyltransferase involved in m6A modification.…”
Section: Discussionmentioning
confidence: 99%
“…In atherosclerosis (AS), the activity of vascular endothelial cells could reflect cells’ metabolism and proliferation [ 17 19 ]. AS is a life-threatening vascular disease, and m 6 A modification level is dysregulated in its pathophysiologic processes of AS [ 20 , 21 ]. Here, we found that m 6 A writer KIAA1429 upregulated in ox-LDL-induced HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…m6A modifications were found to alters HCC progression by affecting immune cell recruitment and pro-tumor inflammation [10]. In addition, m6A modifications altered the proliferation and metastasis of gastric cancer by participating in the infiltration of immune cells and activation of immune pathways [11].…”
Section: Introductionmentioning
confidence: 99%